AL-‘ALAJA AL-NAFSII FII ANA MUTASIF LI SAMIH AL-QASIM - Rahmi Rahmiati; Zulkhairi Sofyan (An-Nahdah Al-'Arabiyah, 2022)
Abstract : This articel aims to examine the Psychotherapy Aspect of a servant in his prayer on Qasidah Samih Al- Qaseem “’Ana muta’assif". In the beginning of Qasidah he starts by calling his God and then complains about his suffering. The poet describes that he really needs help and forgiveness from his God so that the suffering he experiences disappears. And he considers his sin to be the cause of the suffering. This is a new study in literature by looking at the psychological aspects of a servant which is studied with Islamic Psychotherapy Theory which is divided into four sides, namely morals, mental, spiritual, and physical. Abstrak : Makalah ini bertujuan untuk mengkaji Aspek Psikoterapi seorang hamba dalam munajatnya pada Qasidah Samih Al-Qaseem “’Ana Muta’assif” . Dalam permulaan Qasidah ia memulai dengan memanggil Tuhannya dan kemudian mengadu tentang penderitaannya. Penyair menggambarkan bahwa ia sangat membutuhkan pertolongan dan ampunan dari Tuhannya supaya derita yang dialaminya sirna. Dan ia mengganggap bahwa dosanyalah penyebab dari datangnya derita itu. Hal ini menjadi telaah baru dalam sastra dengan melihat aspek psikologi seorang hamba yang dikaji dengan Teori Psikoterapi Islam yang terbagi pada empat sisi yaitu akhlak, mental, spiritual, dan fisik.